Nurses’ role in compulsory notification of domestic violence in a Basic Health Unit - Reis, Lindaiane Tamires de Lima; Martins , Vanessa; Santos , Janici Therezinha; Flores , Pericles Cristiano Batista; Magalhães, Plinio Regino (Seven Editora, 2024)
In Brazil, in July 2022, 31,000 reports of domestic violence were registered, a problem that has serious consequences, such as psychological, physical, financial damage and even the death of the women involved. To address this reality, policies such as the Maria da Penha Law (Law 11,340) were implemented to protect victims. The need for health strategies then arose, resulting in the development of the Notifiable Diseases Information System (SINAN), driven by health professionals through Compulsory Notifications. This article, based on a literature review, used sources such as books, dissertations, scientific articles and online databases (Google Scholar, Scielo, VHL). The analysis covered the last five years (2018-2023), including laws prior to that period (2006-2015). Violence against women ranges from harassment to femicide, and access to health services is often intermediated by basic health units. Nursing care begins with welcoming, where nurses play a crucial role as health educators, contributing to the recovery, empowerment and well-being of patients, in addition to dealing with the alarming statistics of this type of violence. Despite the advances made by the Maria da Penha Law, domestic violence against women in Brazil persists as a serious problem, as shown by statistics from the Ministry of Human Rights and Citizenship. Addressing this phenomenon remains challenging, especially with regard to the proper identification and notification of cases. DOI:https://doi.org/10.56238/sevened2024.010-068